Study on the influence of international oil price on domestic oil price by APT-ECM. Issue 1 (July 2021) - Liu, Ziyuan; Wang, Yu; Xu, Shiwei; Wang, Shengwei; Li, Denghua; Zhou, Han
Abstract: Based on the monthly data of soybean, soybean oil and soybean meal prices in China and the United States from 2006 to 2020, this paper applied the asymmetric error correction model (APT-ECM) to analyze the influence of international oil price on domestic oil price before and after Sino-US trade friction. The results show that: 1) the influence of international domestic soybean price on domestic soybean price is significant before and after Sino-US trade friction, while the influence of domestic price on international price is insignificant; 2) the impact of international soybean oil price on domestic soybean price is stable in the early stage but fluctuates evidently in the latter stage; 3) domestic soybean oil price is exposed to insignificant impact of international soybean oil price.